Basic and Advanced Metal-Artifact Reduction Techniques at Ultra-High Field 7-T Magnetic Resonance Imaging—Phantom Study Investigating Feasibility and Efficacy. Issue 6 (13th June 2022) - Germann, Christoph; Falkowski, Anna L.; von Deuster, Constantin; Nanz, Daniel; Sutter, Reto
Abstract : Objectives: The aim of this study was to demonstrate the feasibility and efficacy of basic (increased receive bandwidth) and advanced (view-angle tilting [VAT] and slice-encoding for metal artifact correction [SEMAC]) techniques for metal-artifact reduction in ultra-high field 7-T magnetic resonance imaging (MRI). Materials and Methods: In this experimental study, we performed 7-T MRI of titanium alloy phantom models composed of a spinal pedicle screw (phantom 1) and an intervertebral cage (phantom 2) centered in a rectangular LEGO frame, embedded in deionized-water-gadolinium (0.1 mmol/L) solution. The following turbo spin-echo sequences were acquired: (1) nonoptimized standard sequence; (2) optimized, that is, increased receive bandwidth sequence (oBW); (3) VAT; (4) combination of oBW and VAT (oBW-VAT); and (5) SEMAC. Two fellowship-trained musculoskeletal radiologists independently evaluated images regarding peri-implant signal void and geometric distortion (a, angle measurement and b, presence of circular shape loss). Statistics included Friedman test and Cochran Q test with Bonferroni correction for multiple comparisons. P values <0.05 were considered to represent statistical significance. Results: All metal-artifact reduction techniques reduced peri-implant signal voids and diminished geometric distortions, with oBW-VAT and SEMAC being most efficient. Compared with nonoptimized sequences, oBW-VAT and SEMAC produced significantly smaller peri-implant signal voids (all P ≤ 0.008) and significantly smaller distortion angles ( P ≤ 0.001). Only SEMAC could significantly reduce distortions of circular shapes in the peri-implant frame ( P ≤ 0.006). Notably, increasing the number of slice-encoding steps in SEMAC sequences did not lead to a significantly better metal-artifact reduction (all P ≥ 0.257). Conclusions: The use of basic and advanced methods for metal-artifact reduction at 7-T MRI is feasible and effective. Both a combination of increased receive bandwidth and VAT as well as SEMAC significantly reduce the peri-implant signal void and geometric distortion around metal implants.